ON THE TAXONOMY AND EVOLUTION OF SAMOTHERIUM (GIRAFFIDAE, ARTIODACTYLA) - Godina A.Ya. (My University, 2002)
Based on the examination of cervical vertebrae 1-4, a new species, Samotherium borissiaki sp. nov., from the Meotian of the Taraklia locality (Moldova) is described. The first and second vertebrae are of special interest, because their evolutionary changes are closely associated with changes in the occipital region of skull and are attributable to the mode of feeding, namely, to the elevated or lowered position of head during foraging. As samotheres adapted to various forest-steppe biotopes, they diverged to form three ecological groups. Chersonotherium eminens Alexejev is divided into two species, Samotherium eminens and S. korotkevichae sp. nov.